2011
DOI: 10.15288/jsad.2011.72.361
|View full text |Cite
|
Sign up to set email alerts
|

Racial Prejudice and Unfair Treatment: Interactive Effects With Poverty and Foreign Nativity on Problem Drinking

Abstract: ABSTRACT. Objective: Although racial and ethnic minorities are often disadvantaged in multiple ways, little research has examined the interactive effects of multiple forms of disadvantage in these populations. The current study describes the independent and interactive effects of perceived prejudice, perceived unfair treatment, poverty, and foreign nativity on problem drinking outcomes among Black and Latino adults. Method: The data source was Black (n = 504) and Latino (n = 766) drinkers from the nationally r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 62 publications
5
62
0
Order By: Relevance
“…These fi ndings are in keeping with those of Dawson and colleagues (2005), who showed that poverty exacerbates the effects of job-related stressors on drinking frequency and alcohol consumption among past-year drinkers. They are also in line with our prior fi nding that poverty intensifi es the effects of unfair treatment and racial stigma on drinking outcomes, particularly among Hispanics (Zemore et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These fi ndings are in keeping with those of Dawson and colleagues (2005), who showed that poverty exacerbates the effects of job-related stressors on drinking frequency and alcohol consumption among past-year drinkers. They are also in line with our prior fi nding that poverty intensifi es the effects of unfair treatment and racial stigma on drinking outcomes, particularly among Hispanics (Zemore et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…One exception was our previous study of African Americans and Hispanics showing that poverty exacerbates the effects of social adversity on drinking outcomes, particularly among Hispanics (Zemore et al, 2011). More often, alcohol studies of differential vulnerability have compared racial/ethnic minorities with Whites.…”
Section: The Question Of Differential Vulnerabilitymentioning
confidence: 96%
See 1 more Smart Citation
“…The transformed score was centered around the sample mean for use in interaction with job loss (Aiken & West, 1991). The three-item measure is associated with reporting greater negative alcohol-related consequences Zemore et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…To date, no studies have examined the role of racial stigma in explaining the effects of job loss on alcohol outcomes in a large and racially/ethnically diverse sample as we do in the current analysis. Previous studies have largely focused on the role of racial stigma in explaining alcohol outcomes (Mulia & Zemore, 2012;Zemore et al, 2011).…”
Section: Job Loss Alcohol Consumption and Alcohol Problemsmentioning
confidence: 99%